Nilai Kebebasan sebagai Wujud Protes dalam Puisi Karya Wiji Thukul dan Chairil Anwar: Kajian Analisis Break - Nesti, Meksi Rahma; Pendri, Apri (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Gender inequality often occurs in women. This is because the construction of a patriarchal society places This research aims to describe the spirit and essence of Wiji Thukul's poem entitled Warning and Chairil Anwar's poem entitled Aku. This poem is the most popular compared to other poems. Apart from that, these poems have made the poet's name still known today. The discussion of this paper uses the BREAK theory. BREAK is an abbreviation for Discourse Basis, Discourse Relations, Discourse Equilibrium, Discourse Actualization, and Discourse Sustainability. This theory was designed by Sawirman as a response to the limitations of Kantian, Hegelian, and Marxian dialectics in describing the typology of movements and structures of change in reality and discourse in a way that can accommodate. The focus of this theory is to explain linguistic phenomena while considering changes in essence and spirit in discourse. Furthermore, the method used in this research adopts a qualitative method. A qualitative research method is an approach that produces descriptive data in the form of written or oral data. Then, the data analysis carried out in this research uses the help of semiotic theory introduced by Saussure and stylistic concepts related to the use of figures of speech. This research provides an analysis that Wiji Thukul's poetry (as primary discourse) and Chairil Anwar's (as secondary discourse) have different discourse essences. The results of this research found that in the primary discourse, there is a spirit of collective freedom, while in the secondary discourse there is a spirit of individual freedom. Meanwhile, the spirit of the primary discourse is a warning to the authorities and an effort to raise the spirit of the people and the spirit of the secondary discourse is that freedom must be obtained by humans at the individual level.